Pemodelan Hidrograf untuk Menilai Pengaruh Perubahan Penggunaan Lahan Terhadap Karakteristik Aliran Sungai Di Sub-DAS Tanralili, Sulawesi Selatan (Hydrograph Modeling to Assess the Impact of Land Use Changes on River Flow Characteristics in the Tanralili Sub-Watershed, South Sulawesi) - Sartika Laban; Hazairin Zubair; Fajar Nugraha; Nurul Fajeriana (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2025)
The Tanralili sub-watershed is part of the Maros watershed, located in South Sulawesi, which plays a crucial role in maintaining an important ecosystem function. However, it has experienced a decline in quality due to land cover change, such as deforestation. This study aimed to assess the physical characteristics of the Tanralili sub-watershed area that affect the variability of stream flow components, analyse land cover changes, calculate the magnitude of flow components, and evaluate the impact of land cover change on the hydrological response of the sub-watershed. The data used included land cover, rainfall, river water levels in 2011 and 2022, and soil types. The straight-line hydrograph method was used to analyse the river flow components, namely surface flow, interflow, and base flow. The results showed an increase in surface flow of 85.43% and a decrease in base flow of 65.12%. This change is related to the conversion of forests into agricultural land and settlements, as well as variations in rainfall that affect the watershed’s hydrological response. These changes increase the potential risk of flooding during the rainy season and droughts during the dry season. Therefore, the importance of upstream area conservation and land conversion control as part of hydrological risk mitigation strategies and sustainable water resources management in the Tanralili Sub-watershed. Although this study suggests that the hydrograph approach can be used to detect the impact of land use change on river flow dynamics,